2018
DOI: 10.3892/etm.2018.6980
|View full text |Cite
|
Sign up to set email alerts
|

The impact of lifestyle factors on evolution of atopic dermatitis: An alternative approach (Review)

Abstract: Atopic dermatitis (AD) is a multifactorial chronic inflammatory disease with an incompletely understood etiopathogenesis. With a significant impact on the quality of life of patients, AD has attracted the interest of many research studies aiming to investigate the complex cellular and molecular mechanisms and to identify new therapeutic pathways. Various studies have focused on psycho-immunology, emphasizing the involvement of stress, defined as a general response of the body to external or internal challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 78 publications
1
45
0
2
Order By: Relevance
“…Another mechanism implicated in DA is the dysfunction of the epidermal barrier. By disrupting this barrier, antigens can penetrate the skin and generate the production of inflammatory cytokines that support the underlying mechanism of the pathology (1).…”
Section: Introductionmentioning
confidence: 99%
“…Another mechanism implicated in DA is the dysfunction of the epidermal barrier. By disrupting this barrier, antigens can penetrate the skin and generate the production of inflammatory cytokines that support the underlying mechanism of the pathology (1).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we have not taken into consideration in this analysis other photoprotection measures different from sunscreen (clothes, avoidance sun exposure) or sedentary lifestyle that could also influence serum VD levels and perhaps AD severity. 40 In conclusion, although serum 25(OH)D levels in AD patients were comparable to those of healthy controls, disease severity was inversely associated with serum 25(OH)D levels in patients with light phototypes. For those with dark phototypes, this association was only detected for those with markers of allergy.…”
Section: Studies Of the Relationship Between Other Atopic Diseases Anmentioning
confidence: 70%
“…Another limitation of the study is that patients with AD were recruited in pediatrics and dermatology clinics; therefore, children with mild AD can be underrepresented. Finally, we have not taken into consideration in this analysis other photoprotection measures different from sunscreen (clothes, avoidance sun exposure) or sedentary lifestyle that could also influence serum VD levels and perhaps AD severity …”
Section: Discussionmentioning
confidence: 99%
“…Atopic dermatitis falls into suicide risk dermatological diseases. In the spring, exacerbation of atopic conditions may increase the risk of suicide (36,37). Halvorsen et al (38) reported the presence of suicidal ideation in 15.5% of those studied with dermatitis vs. 9.1% of those who did not have dermatitis.…”
Section: Dermatological Conditions With Increased Risk Of Suicidal Bementioning
confidence: 99%